Slovenski jezik na stičišču več kultur - Marina Bajić; Jesenšek, Marko (2014)
Slovenian Language at the Crossroads of Several Cultures. The Slovenian profession must (1) ensure the functional integrity of the Slovenian language in the common European linguistic and university space; (2) to promote the linguistic diversity of Slovene and dialects in the region and region across the border; (3) consolidate the position of the Slovenian language as the official language of the European Union and create opportunities for increased interest in learning our language; (4) to provide quality instruction in Slovenian, foreign languages ​​and translation at our schools and faculties. In the scientific field, original research into the Slovene language in the border area opens new perspectives on the development of the Slovene language, establishes new frameworks for defining linguistic norms and regulations, and above all promotes regional integration (the Danube region and the Alps-Adriatic region) and solves in the past over-neglected issue of linguistic minorities and cross-border linguistic interconnection of Slovene language in contact with other regional languages ​​of this region. encouraged the recognition that Slovenians in the European Union can be recognized first and foremost by language.